2020
DOI: 10.18553/jmcp.2020.26.11.1477
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and gender disparities in the use of erythropoiesis-stimulating agents and blood transfusions: cancer management under Medicare’s reimbursement policy

Abstract: BACKGROUND: Because of increasing safety concerns related to erythropoiesis-stimulating agents (ESAs), the Centers for Medicare & Medicaid Services issued a Medicare reimbursement policy change regarding these medications in cancer patients. However, the policy established an absolute hemoglobin or hematocrit threshold to qualify for reasonable use but did not take the effect of gender and racial/ethnic differences in hemoglobin levels into consideration. OBJECTIVE: To examine disparities in the use of ESAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previous studies have similarly found widening disparities owing to NCD policy implementations, although potential explanations have not been elucidated. 31 , 32 In these studies, the purpose of the NCD was to restrict the use of certain procedures and treatments to avoid negative outcomes, which disproportionately affected certain populations. 31 , 32 In contrast, the NGS NCD was intended to enable access to a technology deemed reasonable and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have similarly found widening disparities owing to NCD policy implementations, although potential explanations have not been elucidated. 31 , 32 In these studies, the purpose of the NCD was to restrict the use of certain procedures and treatments to avoid negative outcomes, which disproportionately affected certain populations. 31 , 32 In contrast, the NGS NCD was intended to enable access to a technology deemed reasonable and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients who were female and of racial/ethnic minorities, patients who were male and who were White were less likely to use alternative strategies (eg, blood transfusion) to manage anemia when ESAs were not provided. 20 Medical costs of alternative strategies and their complications might have offset the reduction in ESA costs.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Arneson et al, Hershman et al, and Li et al found that the use of ESAs had a 50%-57% reduction after the policy change based on claims. [18][19][20] Specifically, Li et al identified racial/ethnic and sex disparities in the impact of the policy change on the use of ESAs. 20 Before the reimbursement policy change, Medicare paid approximately $2 billion every year to reimburse for ESAs.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of relevant research, Li et al (2020) explored the effect of a Medicare reimbursement policy change on the use of erythropoiesis-stimulating agents (ESAs) and blood transfusions in this month's issue. 2 The policy had the intended effect of reducing ESA use by 50% in all race and ethnicity groups. However, there was an unintended effect of increasing blood transfusions, which was of a higher magnitude in the Black population (50%) compared with the full study cohort (10%).…”
Section: Call For Submissionsmentioning
confidence: 99%